The Effect Of The Role Of Reproduction Health Knowledge On The Sexual Behavior Of Early Adolescents - Dian Permatasari; Emdat Suprayitno; Qurratul A'yun (Jurnal Keperawatan Terpadu (Integrated Nursing Journal), 2022)
This study aims to determine the role of reproductive health knowledge with early adolescent sexual behavior in Patian Village. The sample in this study amounted to 103 people who were taken by purposive sampling technique. Methods of data collection using a sexual behavior scale and reproductive health knowledge questionnaire. Based on a simple linear regression test, a significance value of 0.033 with R = -0.207 , and the value of the equation Y = 89.679 + - 1.040X, which means knowledge of reproductive health has a negative role on sexual behavior so that every increase in knowledge of reproductive health by one point (eg 89.679 -> 90,679), then sexual behavior will decrease by -1,040. In addition, an R Square of 0.043 indicates that knowledge of reproductive health has a role contribution to sexual behavior by 4.3%. Thus it can be concluded that there is a negative role of reproductive health knowledge on sexual behavior, so the higher the knowledge of reproductive health, the lower the sexual behavior of early adolescents in Patian Village.